Pengembangan Bahan Ajar Simulasi Digital Bermuatan Model Edutainment untuk Menumbuhkan Keaktifan Belajar Siswa Kelas X TKJ di SMK Negeri 2 Turen - Joyo, Achmad Darmo; Putro, Setiadi Cahyono; Herwanto, Heru Wahyu (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Based on an interview, 88 percent from 34 students received a score below the minimal completeness criteria in Digital Simulation subject because students were passive in the learning and the usage of uninteresting learning material. This developmental research aimed to design and develop the mobile-based digital simulation learning material to improve students' activeness in Class X TKJ, Public High School Vocational High School 2 Turen and tested the feasibility of teaching materials as learning supplements. This research used the ADDIE model, containing: (1) analyze, (2) design, (3) develop, (4) implement, and (5) evaluate. The feasibility test was performed in Class X TKJ students in Digital Simulation subject. Based on the obtained data, the material validation test from experts was 95 percent, media test from experts obtained 98.74 percent, small group test was 91.2 percent, and field test obtained 94.65 percent. It could be concluded that Simulation Digital learning material was in very feasible category.